Evaluation of targeted oxidative stress induced by oxygen-ozone in vitro after ischemic induction - Jessica Rodrigues Orlandin; Sarah Ingrid Pinto Santos; Luciana Cristina Machado; Paulo Fantinato Neto; Fabiana Fernandes Bressan; Naira Caroline Godoy Pieri; Kaiana Recchia; Meline de Paula Coutinho; Priscilla Avelino Ferreira Pinto; Annalisa Santucci; Valter Travagli; Carlos Eduardo Ambrosio (Taylor & Francis Group, 2022)
Encephalic vascular accident, or stroke, is the most common pathology of the central nervous system in humans, the second leading cause of death and physical and cognitive disabilities, in developing countries. It presents as an ischemic (more common) or hemorrhagic form. Ozone therapy has been shown to be effective in neuromodulation, neuroprotection, and nerve regeneration. The present study aimed to evaluate the effect of targeted mild ozone after inducing cerebral ischemia in vitro. Neuroblastoma lineage cells (SH-SY5Y) and canine amniotic membrane stem cells were subjected to 24 hours of hypoxia in an incubator culture chamber. The cells were evaluated by MTT assay, colorimetric assay spectrophotometry, fluorescence microscopy, and flow cytometry. Treatment with low concentrations of ozone (2-10 µg/mL), indicated a possible neuroregenerative effect at low concentrations, correlated with lower levels of apoptosis and oxidative stress compared to cells not subjected to hypoxia. High concentrations of ozone (18-30 µg/mL) promoted an increase in rate of apoptosis and cell death. We developed a novel protocol that mimics ozone therapy for ischemic stroke, using ozonized culture medium after hypoxia induction. Although more studies are needed, we conclude that ozone has a dose-dependent hormetic effect and can reverse the effect of ischemia in vitro at low concentrations.